2015
DOI: 10.14257/astl.2015.88.38
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Core Stability Training on Postural Control Ability and Respiratory Function in Chronic Stroke Patients

Abstract: The purpose of this study was to examine the effects of the core stability training on postural control ability and respiratory function in chronic stroke patient. Experimental group (n=15) received core stability training. Control group (n=15) received general exercise. We measured maintenance and change of posture, balance and coordination ability with postural assessment scale for stroke (PASS) and trunk impairment scale (TIS). The respiratory functions were measured forced vital capacity (FVC), forced expi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…However, it is easy to overlook because the physical motor deficit caused by hemiplegia is prominent and the change in respiratory function that occurs after stroke may not cause acute respiration disease. Furthermore, stroke causes physical disorders accompanied by decreased flexibility and muscle weakness, and asymmetric breathing is caused by an increase in sensitivity to carbon dioxide and a decrease in voluntary breathing, which can change respiration control [19][20][21].Since respiration is one of the most important functions for human life, patients' functional ability must be assessed, to diagnose disease and to investigate the prognosis with cardiopulmonary function measurements.Aging can change sensorimotor processing, and the older neuromuscular system is weakened by 40% compared to normal healthy adults [22].Generally, stroke, which occurs in the middleaged and older population, is a neurological disorder and shows diverse symptoms such as decreased sensorimotor function, perception, cognition, verbal function, and psychological disorder. Moreover, many patients have permanent disability without the recovery of function [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is easy to overlook because the physical motor deficit caused by hemiplegia is prominent and the change in respiratory function that occurs after stroke may not cause acute respiration disease. Furthermore, stroke causes physical disorders accompanied by decreased flexibility and muscle weakness, and asymmetric breathing is caused by an increase in sensitivity to carbon dioxide and a decrease in voluntary breathing, which can change respiration control [19][20][21].Since respiration is one of the most important functions for human life, patients' functional ability must be assessed, to diagnose disease and to investigate the prognosis with cardiopulmonary function measurements.Aging can change sensorimotor processing, and the older neuromuscular system is weakened by 40% compared to normal healthy adults [22].Generally, stroke, which occurs in the middleaged and older population, is a neurological disorder and shows diverse symptoms such as decreased sensorimotor function, perception, cognition, verbal function, and psychological disorder. Moreover, many patients have permanent disability without the recovery of function [23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to enhance pulmonary function, functions of the major respiratory muscles that directly expand the thorax and the respiratory support muscles that help thoracic expansion by lifting the thorax need to be improved. Major respiratory muscles include the diaphragm, intercostal muscles, and abdominal muscles 3 ) that are involved in resting respiration 4 ) . Respiratory support muscles include the sternocleidomastoid (SCM), scalene, trapezius, pectoralis major, pectoralis minor, and anterior serratus 5 ) , which are involved in deep, forced breathing 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Marshall(2005) showed that core stabilization exercise using swiss ball make considerable increase of activities of rectus abdominis [11]. Also, it is reported that stabilization exercise is effective on pain control and functional recovery of patient during long term [25][26][27]. That is, the stabilization exercise of the shoulders have a positive effect on the pain and function.…”
Section: Discussionmentioning
confidence: 97%